STUDI TENTANG BURUH TANI PEREMPUAN DI DESA SUKAMAJU KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Umi Musallamah; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Sukamaju village is the village of transmigration general public placement imported from Java Island; West Java, Central Java, and East Java. Sukamaju village is dominated by oil palm plantations, so that many people who work as farm laborers of palm included in this study are housewives. Work carried out by female workers, more dominant on the part of treatment. Type of work is the provision of palm fertilizer (nurture), picking up a fallen palm fruit, palm pest poison (spraying), and mow the weeds around the palm tree (chop).With the employment of the villagers Sukamaju take advantage of opportunities or employment opportunities, causing a lot of people who are interested to become laborers, including women. In addition, there are other reasons why women choose to work as laborers which are due to environmental factors (comfort in the workplace and their family support), the desire factor and the most important is the economic factor. According Wiliam J. Goode, women worked mainly due to poverty. The tendency for women to work is also due to economic factors. The location of this study conducted in Sukamaju village, Singingi Hilir district, Kuantan Singingi regency. The population in this study is housewives who work as farm laborers of palm, sampling technique that used in this study is senses method, the sampling technique when all members of the population used as a sample. In this study a population of female respondents as many as 42 people so that all the population sampled. Analysis of the data that used is a descriptive analysis of quantitative data. Where the content of this study contains a discussion of the result of the research is in depth explanation and interpretation of the data that has been represented. After a discussion of the results is given, then the next can be inferred. From the research results can be seen that women who go to work as laborers due to the economic demands, they are required to supplement the family income. Moreover, the desires to send their children to college also cause women to work, although only as laborer palm.Keywords: Social Conditions, Women’s work